Comparison of Taclorimus Ointment versus Kenalog in Ora Base for the Treatment of Oral Lichen Planus - Ahmed, Mansoor; Khan, Aimal (Indus Journal of Bioscience Research, 2025)
Background: Oral lichen planus (OLP) is a chronic, mucocutaneous condition that exhibits painful erosive or reticular lesions on the oral mucosa. Typically, treatment consists of topical corticosteroids (e.g. triamcinolone in Ora base. Tacrolimus, a calcineurin inhibitor, has been suggested as an effective substitute, especially among those that are steroid resistant; however, comparative clinical evidence is scarce. Objectives: The aim of the study was to examine and compare efficacy, safety of tacrolimus ointment and Kenalog in Ora base in patients with symptomatic oral lichen planus (OLP) for response, tolerability, and recurrence. Study Design: A prospective study. Place and duration of study: Department of Oral & Maxillofacial Surgery, Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta, from February 2025 to May 2025. Methods: A randomized controlled prospective study clinical trial was performed on hundred patients with oral lichen planus symptomatology. Patients were randomized into 2 groups: Group A: tacrolimus 0.1% ointment and Group B triamcinolone acetonide (Kenalog) in Ora base both applied three times daily for six weeks. The outcome was measured by the severity of symptoms, decrease in the size of the lesions and side effects. Data analysis was done using SPSS v24. 0 to p < 0.05. Results: The mean age of 100 patients (52 males, 48 females) was 46.7 ± 11.2 years. There was significantly more improvement in pain reduction and resolution of lesion in Group A (tacrolimus) than with Group B (Kenalog). 40% in the tacrolimus group versus 22% in Kenalog. Partial response was observed in 46% vs 52%, respectively. Non-responders were 14% vs 26%. Burning upon application was more common with tacrolimus use and it was short lived. Mean decrease in clinical score was statistically significant overall (p = 0.003) for exercise plus tacrolimus treatment vs control. Conclusion: Tacrolimus ointment achieved better symptomatic improvement and higher remission than Kenalog in Ora base for patients with oral lichen planus. Transient burning was noted, however stopped spontaneously and the participant decided to continue. Kenalog in Ora base was effective but with lower rates of complete remission. It may be an effective and well-tolerated alternative in recalcitrant situations. Chronic studies are needed to confirm long-term efficacy and safety.